The Role of the Gingival Phenotype in Orthodontic Treatment Planning and Complication Risk Stratification: A Review - Odnoralov, Антон (Actual Dentistry, 2026)
Abstract. The gingival phenotype is a key determinant of the periodontal response to orthodontic loading, the limits of safe tooth movement, and the risk of mucogingival and aesthetic complications. A thin gingival phenotype combined with a thin vestibular cortical plate is regarded as a major risk factor for the development of gingival recession, dehiscence, and fenestration, particularly in the anterior region. Objective. To synthesize contemporary evidence regarding the concept and classification of the gingival phenotype in the context of orthodontic treatment; to summarize diagnostic approaches for evaluating the gingival phenotype and alveolar bone morphotype; and to clarify the role of the gingival phenotype as a risk factor for mucogingival complications during orthodontic therapy. Material and Methods. A narrative-analytic literature review was conducted with targeted searching of clinical and experimental studies in PubMed/MEDLINE, Scopus, Web of Science, Google Scholar, and Ukrainian scientific repositories for the years 2020—2025. Included in the analysis were original clinical studies, prospective and retrospective observational studies, systematic reviews, meta-analyses, clinical practice guidelines, and expert consensus reports. Results. Systematic reviews confirm that a thin phenotype, a narrow band of keratinized gingiva, baseline recession, and inflammation are significant predictors of new recession development or progression of existing defects during and after orthodontic treatment. Excessive vestibular proclination, particularly of the mandibular incisors, is considered a key modifiable risk factor, whereas the type of orthodontic appliance (brackets versus aligners) does not demonstrate an independent effect when adequate oral hygiene is maintained. Risk stratification is most appropriately performed across three groups: a thin phenotype with a thin bone morphotype (high risk), an intermediate phenotype (moderate risk with localized “weak zones”), and a thick phenotype (relatively favorable but not risk-free). Conclusions. The gingival phenotype is a crucial predictor of periodontal response to orthodontic interventions and the development of mucogingival and aesthetic complications. Assessment of the gingival phenotype and alveolar morphotype should constitute an obligatory component of the initial diagnostic protocol for orthodontic patients, using a combination of clinical and three-dimensional radiographic methods. A thin phenotype associated with thin vestibular bone requires limitation of vestibular and inclination movements, strict torque control, individualized retention strategies, and enhanced periodontal monitoring. Even in patients with a thick phenotype, meticulous hygiene and adherence to the anatomical boundaries of the alveolar housing remain essential.